2-stage progressive-die hot stamping of ultra-high strength steel parts using resistance heating. (2017) - Mori, Ken-ichiro; Maeno, Tomoyoshi; Sakagami, Masato; Ukai, Masanori; Agatsuma, Yuki
Abstract: A 2-stage progressive-die hot stamping process using partial resistance heating was developed to produce a small-sized ultra-high strength steel parts without additional heat treatments. In the 1st stage, a uncoiled long plate was successively heated by partial resistance heating, and then is simultaneously blanked and punched. The blank is inserted in the blanked plate to be conveyed. In the 2nd stage, the blank is bent and die-quenched. The resistance heating and die quenching operations are synchronised to double the productivity. An automobile seat belt buckle having 1500 MPa in tensile strength was successfully produced without springback.